If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = x + (-5) 7 = x + -5 Reorder the terms: 7 = -5 + x Solving 7 = -5 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 7 + -1x = -5 + x + -1x Combine like terms: x + -1x = 0 7 + -1x = -5 + 0 7 + -1x = -5 Add '-7' to each side of the equation. 7 + -7 + -1x = -5 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = -5 + -7 -1x = -5 + -7 Combine like terms: -5 + -7 = -12 -1x = -12 Divide each side by '-1'. x = 12 Simplifying x = 12
| 5x+20y=250 | | 5x+5(5x+3)=74 | | 36x^2+15x-3=270 | | -7(x+3)=56 | | 550=(175)(7)+b | | -9=x-25 | | -2=x-723 | | 4x/x=16 | | -3(4x+1)=69 | | 1-8=623+x | | 58-6-x+51-3=55 | | -14-x=20 | | 0.5x-7=1.5x-1 | | 5e^2x+16=41 | | x+2x+3x=150 | | 4x-5x+x=11x-3 | | 3/5/9 | | (3/2)-4x=(1/2) | | -2(4x-1)=5(2x-5) | | -11x+5=14x | | 3/5x9 | | x-23=-78 | | x(7)=(17)(8) | | 170+0.25=365 | | x/(7)=(17)/(8) | | 3(2x-5)=6(x-2) | | 3.5-4x=0.5 | | -2x+1+x=5-4-x | | 17/8=x/7 | | 7*a-4=31 | | -(3x-26)=2(x+3) | | 3s+50=4s+45 |